Analysis of Mec-A Gene on Methicillin Resistant Staphylococcus aureus - Suliati Suliati; Ayu Puspitasari; Anita Dwi Anggraini (Health Notions, 2023)
The prevalence of MRSA in various hospitals in the world ranges from 2-70% with an average of 20% .In recent decades there has been an increasing prevalence of S. aureus and MRSA in the world. Population-based studies in North America and Europe indicate the prevalence of S. aureus is between 18-30%. The overall prevalence of MRSA in Asia has reached 70%, while publications and prevalence of MRSA in Indonesia are still very limited and very difficult to obtain. The prevalence of MRSA in Atmajaya Hospital, Jakarta, reached 47%. Yuwono also reported in 2010 MRSA at Dr. RSUP. Moh. Hoesin Palembang reached 46%. Amplification were carried out under PCR conditions as a result of optimization, namely the results of PCR optimization were carried out for 30 cycles with the following thermal conditions. Denaturation phase at 94oC for 30 seconds, annealing at 52.0oC for 30 seconds, and extension at 72oC for 1 minute. Amplification results showed that of the 30 samples only 90% (27 samples) were detected to have the Mec-A gene, 10% (3 samples) were negative. Keywords: Mec-A; gene; Methicillin Resistant Staphylococcus aureus